Tics and TikTok: Functional Tics Spread Through Social Media. Issue 8 (1st July 2021) - Hull, Mariam; Parnes, Mered
ABSTRACT: Background: Functional movement disorder is a subtype of functional neurologic symptom disorder a syndrome of involuntary physical, neurologic‐type symptoms that are incongruous with "organic" disease. Throughout history, there have been outbreaks of functional symptoms in communities; until recently, spread had been confined to groups of people who shared a physical location. However, in the era of social media, a new mode of dissemination may have arisen. Cases: We describe six teenage girls, each with the explosive onset of tic‐like movements. Mean age of onset was 14.2 years. The presence of features incongruous with Tourette syndrome on history and examination prompted the diagnosis of functional tics. All patients reported exposure to a specific social media personality before symptom onset. Conclusions: Our series suggests that social media may contribute to the spread of functional neurologic symptom disorder, in a way previously requiring physical proximity.